Efeito da plataforma vibratória na remobilização de ratos wistar - Wutzke, Maria Luiza Serradourada (2020)
Immobilization is used to treat musculoskeletal injuries, however, it triggers adaptive changes in different organ systems that lead to functional loss. In an attempt to recover muscle, functional and nociceptive damage, physical exercises are widely used. However, there are still gaps as to the type of remobilization protocol most effective for remobilization. An alternative therapeutic modality that has been used is mechanical vibration, through the vibrating platform, as it promotes significant gains in muscle trophism and function. The present study aims to compare the effects of isolated free remobilization, with the effects of free remobilization associated with the vibrating platform on nociception, functionality and morphology of the soleus muscle of Wistar rats. For that, 28 rats were randomly divided into four experimental groups (n = 7): CG (Control); IG (immobilized only), immobilized according to standard protocol; GRL (free immobilization and remobilization); GRPV (immobilization and remobilization with vibrating platform). For platform remobilization, the frequency of 60 Hz was used for 10 minutes, five days a week, for two weeks. The nociception of the right posterior paw was assessed before immobilization, before and at the end of the treatment with vibration. Just like filming for the IFA. After the experimental period, the animals were properly euthanized, and the right soleus muscles were dissected for histomorphometric analysis. The soleus muscle was analyzed for length and changes in muscle fiber, by analyzing the crosssectional area, larger and smaller diameter, quantity of fibers, number of cores and ratio of cores to fiber. The amount of capillary and the capillary to fiber ratio were also analyzed. From the analyzes of the GRL and GRPV groups, it was observed that for the nociception variable there was a reduction in the threshold caused by immobilization and an increase after remobilization. In the functional evaluation, the immobilized animals reduced the function while the remobilized animals obtained improved functionality. There was an increase in the length of GRL compared to the CG and the GI, in addition, the GRPV was greater than the GI group. From the morphometric analysis, it was observed that the immobilization reduced the area, larger and smaller diameter of the muscle fiber compared to the CG. GRPV increased the area and larger diameter compared to GRL. The IG had more fiber than GC, GRL and GRPV. GI also had more nuclei than GC, a reduction in nuclei was observed in the remobilized groups when compared to GI. Regarding the ratio of capillaries to fibers, the GRPV had higher values than the other groups, hearing an increase in connective tissue in GI compared to CG, the remobilized groups had more connective tissue than the CG and less than the control. With this work, it is concluded that immobilization causes functional damage, increased nociceptive threshold and damage to the soleus muscle. The vibrating platform is effective for remobilization.